2006
DOI: 10.3336/gm.41.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Some rational Diophantine sextuples

Abstract: Abstract. A famous problem posed by Diophantus was to find sets of distinct positive rational numbers such that the product of any two is one less than a rational square. Some sets of six such numbers are presented and the computational algorithm used to find them is described. A classification of quadruples and quintuples with examples and statistics is also given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 7 publications
1
47
0
2
Order By: Relevance
“…This was almost proved by Dujella [5], who showed that there can be at most finitely many Diophantine quintuples and all of them are, at least in theory, effectively computable. In the rational case, it is not known that the size m of the Diophantine m-tuples must be bounded and a few examples with m = 6 are known by the work of Gibbs [8]. We also note that some generalization of this problem for squares replaced by higher powers (of fixed, or variable exponents) were treated by many authors (see [1,2,9,13] and [10]).…”
Section: Introductionmentioning
confidence: 99%
“…This was almost proved by Dujella [5], who showed that there can be at most finitely many Diophantine quintuples and all of them are, at least in theory, effectively computable. In the rational case, it is not known that the size m of the Diophantine m-tuples must be bounded and a few examples with m = 6 are known by the work of Gibbs [8]. We also note that some generalization of this problem for squares replaced by higher powers (of fixed, or variable exponents) were treated by many authors (see [1,2,9,13] and [10]).…”
Section: Introductionmentioning
confidence: 99%
“…In the rational case, it is not known if the size m of the Diophantine m-tuples must be universally bounded. A few examples with m = 6 are known by the work of Gibbs [7]. Several generalizations of this problem, when the squares are replaced by higher powers of fixed, or variable exponents, were treated in many papers (see [1], [2], [8], [9]) and [10]).…”
Section: Introductionmentioning
confidence: 99%
“…. , a m } in a commutative ring R with 1 is called Diophantine m-tuple if a i a j + 1 is a perfect square in R for all 1 ≤ i < j ≤ m. Let us mention the most famous historical examples of such sets: the first rational quadruple { 16 } found by Gibbs ( [13]). There exist families of such sets, for instance quadruples {F 2k , F 2k+2 , F 2k+4 , 4F 2k+1 F 2k+2 F 2k+3 } (where F k is k-th Fibonacci number) and {k − 1, k + 1, 4k, 16k 3 − 4k} (which both represent a generalization of the Fermat's quadruple).…”
Section: Introductionmentioning
confidence: 99%